Hukum Islam dan Perubahan Sosial: Telaah atas Ijtihâd Fardi dan Jamâ’i - Bisri, Hasan (TAJDID, 2019)
Scientific and technological development creates so many kinds of new products concerning the telecommunication, automotive industry as well as medicine, technology of food and beverage and cosmetics, that this can cause the changes of social interaction among the society, and consequently, response is needed to face a challenging time and the changes of social life. Meanwhile, the number of texts (nash) of Alquran and hadis (prophetic saying) are limited to give the solution the new problems that appear. Based upon a reality, so this will encourage the attempt to grow and develop the Islamic law through Ijtihad (exerting individual as well as collective effort) being is more dynamic for the sake of the people welfare, fair human right protection, and improvement of the people’s standard of living. The writing tries to describe many kinds of factors of social changes responding to the law needed immediately, and are then followed by a great effort to reform the Islamic law suitable for all the time through ijtihad being more accurate and responsible.